2020
DOI: 10.1001/jama.2020.23027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intravitreous Aflibercept vs Vitrectomy With Panretinal Photocoagulation on Visual Acuity in Patients With Vitreous Hemorrhage From Proliferative Diabetic Retinopathy

Abstract: IMPORTANCE Vitreous hemorrhage from proliferative diabetic retinopathy can cause loss of vision. The best management approach is unknown.OBJECTIVE To compare initial treatment with intravitreous aflibercept vs vitrectomy with panretinal photocoagulation for vitreous hemorrhage from proliferative diabetic retinopathy. DESIGN, SETTING, AND PARTICIPANTSRandomized clinical trial at 39 DRCR Retina Network sites in the US and Canada including 205 adults with vison loss due to vitreous hemorrhage from proliferative d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
3
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(85 citation statements)
references
References 30 publications
3
75
3
4
Order By: Relevance
“…However, recurrent VH occurred at least once in 49% of patients in the aflibercept and in 15% in the vitrectomy group. Therefore, the authors underlined that the study may have been underpowered to detect a clinically important benefit in favor of initial PPV with PRP [ 72 ]. It has to be mentioned that although visual outcomes were not significantly different between treatment groups from 12 weeks through 2 years, additional findings from this study may help clinicians guide therapeutic decisions for individuals with VH.…”
Section: Resultsmentioning
confidence: 99%
“…However, recurrent VH occurred at least once in 49% of patients in the aflibercept and in 15% in the vitrectomy group. Therefore, the authors underlined that the study may have been underpowered to detect a clinically important benefit in favor of initial PPV with PRP [ 72 ]. It has to be mentioned that although visual outcomes were not significantly different between treatment groups from 12 weeks through 2 years, additional findings from this study may help clinicians guide therapeutic decisions for individuals with VH.…”
Section: Resultsmentioning
confidence: 99%
“…They also highlight the potential for type I error within their statistical analysis and so "findings for secondary endpoints should be interpreted as exploratory". 36 TOUCHREVIEWS IN OPHTHALMOLOGY AB showed that there was no statistical difference in visual acuity outcomes between aflibercept versus vitrectomy with PRP. Protocol AB results suggest that aflibercept use was associated with less occurrence of DMO relative to vitrectomy with PRP.…”
Section: The Panorama Studymentioning
confidence: 99%
“…In einer vergleichenden Studie bei Patienten mit Glaskörperblutung wurde die Standardtherapie (ppV mit Endolaser) mit intravitrealen Aflibercept-Gaben verglichen. Dabei zeigte sich in beiden Gruppen nach 6 Monaten ver-gleichbar gute Visusäquivalente, jedoch mehr traktive Netzhautablösungen in der IVOM-Gruppe (22 vs. 13 %) [36]. Die Behandlung einer Glaskörperblutung mit VEGF-Hemmern ist daher ein Risiko und immer mit Unsicherheiten aufgrund des fehlenden Funduseinblicks verbunden.…”
Section: Neovaskularisationsglaukomunclassified